Dataset on the Impact of GO-NGO Support on Crop Intensification and Food Security in Bangladesh - Md. Monirul Islam; Arifa Jannat; Aurup Ratan Dhar (Data in Brief, 2018)
The data used in this article elucidated crop intensification and farmers’ food security status through GO-NGO support in Bangladesh. A total of 200 farmers (100 from non-supported and 100 from GO-NGO supported) were selected for data collection using purposive sampling technique. The collected data showed that GO-NGO support has a significant impact on changes in agricultural enterprises. Majority (63.3%) of the households belong to the low intensity category for non-supported farmers. In case of GO-NGO supported farmers, majority (73.3%) of the households belong to the high intensity category. The food security indices values showed that the food security index for non-supported farm households was 0.97 and for GO-NGO supported farm households, it was 1.07. Keywords: Crop intensification, GO-NGO support, Food security, Bangladesh